Coaching-Based Academic Supervision for junior High School Teachers: From Planning to Evaluation and performance Improvement - Afaidi, Markas Ismi; Bahrun, Bahrun; Rasyid, Suparta; Lismeni, Cut (Edukasi, 2026)
This study examines the planning, implementation, and evaluation of coaching-based academic supervision as an effort to improve teacher performance at the junior high school level. Employing a descriptive qualitative design, the study involved 12 participants consisting of school principals, teachers, and school supervisors. Data were collected over a three-month period through observation, semi-structured interviews, and document analysis using purposive sampling. Data analysis followed an interactive model comprising data reduction, data display, and verification, supported by restatement, analytical description, and interpretation to capture patterns, relationships, and meanings within the supervision process. The findings reveal that (1) supervision planning is systematically conducted at the beginning of the academic year through deliberation, needs analysis, goal formulation, instrument preparation, and scheduling; (2) the implementation of coaching-based academic supervision follows three stages—pre-observation, classroom observation, and post-observation—emphasizing reflective dialogue and collaborative interaction; and (3) evaluation results are utilized to refine supervision programs, address teachers’ instructional challenges, and adjust coaching strategies to support continuous professional development. Overall, the study concludes that coaching-based academic supervision contributes to improved teacher performance through participatory planning, structured and supportive implementation, and reflective evaluation that fosters professional growth and sustainable instructional improvement.